Virulence of Beauveria brongniartii and B. bassiana against Schizonycha affinis white grubs and adults (Coleoptera: Scarabaeidae). (28th November 2014) - Goble, T. A.; Conlong, D. E.; Hill, M. P.
Abstract Two endemic scarab pests, Schizonycha affinis Boheman and Hypopholis sommeri Burmeister (Coleoptera: Melolonthinae) have increased in prevalence in the sugarcane producing regions of the KwaZulu‐Natal Midlands, South Africa. The crop losses associated with their feeding, the failure of chemical insecticides applied for their control, and the recent discovery of Beauveria brongniartii (Sacc.) Petch (Ascomycota: Cordycipitaceae) epizootics on these pests, have generated interest in the development of a mycoinsecticide targeting adults and larvae of these species. Previous research, using microsatellite markers, identified low levels of genetic diversity among isolates of B. brongniartii collected from two field sites where epizootics occurred. The virulence of 21 of these closely related B. brongniartii isolates and two isolates of Beauveria bassiana (Balsamo) Vuillemin was evaluated. Bioassays were conducted against adults and larvae of S. affinis, and adult Tenebrio molitor (L.) (Coleoptera: Tenebrionidae) as a surrogate test insect. The closely related B. brongniartii isolates varied significantly in their virulence towards both S. affinis (50.1–95% mortality) and T. molitor (39–74% mortality), with a number of these not highly virulent against either of these insect species. Those isolates sharing a haplotype did not vary in virulence. Adults of S. affinis were more susceptible than larvae to isolates of B. brongniartii. The median lethal concentration (LC50) required to kill half the adult S. affinis test insects was 7.65 × 106 conidia per millilitre. Schizonycha affinis second instar larvae had a median survival time of 17.5 days when exposed to some B. brongniartii isolates; however, third instars survived significantly longer with a median of 21 days. Third instars exposed to the highest concentration of B. brongniartii isolate HHWG1 survived for a median time of 15 days. Bioassays supported the finding that genetically closely related isolates may vary in their virulence, even if they were obtained from the same field epizootics.